Surface quality of massaranduba wood after sanding with different grit sizes (Research, Society and Development, 2025)
Sanding is essential for achieving high-quality wood surfaces, reducing imperfections, and preparing them for finishes, resulting in greater durability. The present study aimed to analyze the surface quality of massaranduba wood through the roughness parameters Ra, Rq, and Rz after sanding with different grit sizes. Fifty test specimens were evaluated after sanding with grits 80, 120, 180, 220, 320, 400, and 600. Roughness was measured using a drag profilometer (SURFTEST SJ-210) and analyzed through ANOVA and Scott-Knott test (5% significance) using SISVAR software. The results showed that Ra and Rq followed the same pattern, indicating that grit 220 provides a satisfactory surface finish. The Rz parameter exhibited a different pattern, suggesting that the best finish is achieved with grit 400. Roughness progressively decreased with sanding. The 80-120-180-220-320-400 sequence demonstrated the best performance for all studied parameters. It is concluded that sanding up to grit 400 is the most recommended for massaranduba wood, ensuring better surface quality in all evaluated parameters.